Motivational factors and job performance of banking industry employees in Klang Valley / Muhammad Ariff Zaini - Muhammad Ariff , Zaini (2020)
Employees’ job performance has been found decreasing and variation changes from time to time. The main objective of this research is to study the relationship between the working conditions, employees’ satisfaction, salaries and benefits, and achievement/recognition towards the job performance of banking industry employees in Klang Valley. In this research study, a total of two hundred (200) bank employees who work in bank around Klang Valley has been selected as respondents. Descriptive analysis (frequency, mean, and standard deviation) and inferential analysis (Pearson correlation coefficient) were used. Pearson correlation analysis’s result shows a significant relationship between the independent variables (working conditions, employees’ satisfaction, salaries or benefits, and achievement/recognition) and dependent variable (job performance). The conclusion is these selected independent variables are factors that might affect the job performance of banking industry employees in Klang Valley.